An Overview on Black Hairy Tongue Treated Constitutionally Through Homoeopathy–A Case Report (Homoeopathy for All, 2023)
Black hairy tongue is a benign  self-limiting disorder characterized  by hypertrophy of the filiform papil lae of the tongue. In this condition a  brownish-black discoloration of the  papillae occurs.The etiology is still  unclear but the condition is associ ated with numerous predisposing  conditions. Homoeopathic medicine  prescribed after proper casetaking  and repertorization has shown ef fectiveness in treating black hairy  tongue. A 45-year-old woman came  with a complaint of blackish discol oration on tongue. A detailed case  history was taken and after proper  repertorization, the constitutional  medicine was prescribed along with  repeated follow-ups were taken at an  interval of 15 days. The follow-ups  of the patient showed remarkable  improvement in her condition
Keywords: Black hairy tongue; Homoeopathy; Repertorization; Constitutional